Invectivas latinescas. Anatomy of the Expostulatio Spongiae in Defense of Lope de Vega (Castilla. Estudios de Literatura, 2012)
This is a study on the literary controversy prompted in 1617-1618 due to the publication of Pedro de Torres Rámila’s Spongia against Lope de Vega and the anonymous Expostulatio Spongiae, written in order to support Lope. On analysing the particular use of the Latin language in both works, we can prove that a good deal of Expostulatio was made up assembling fragments of, at least, five contemporary Latin works. That discovery allows us to propose, as well, a hypothesis on a possible author of Expostulatio.